RADIATION: THE TENSION BETWEEN THE IONIZING RADIATION AND THE BIOLOGICAL EFFECT (Fiep Bulletin - online, 2014)
Ionizing radiation is due to the transmission of energy of a system for another by means of electromagnetic waves. The reaction of the shock provokes or generates the jump of the electron liberating an energy as Rays X and Gamma rays. In reason of the several diseases or lesions provoked by the radiation of the type ionizing, they are the original of the radiation type, of the reached depth, of the area or volume of the exposed body, of the received total dose and of the time of irradiation, that address more concretely in direction to the possible preventive therapies. It is opportune to stress on the ionizing radiations, when crossing woven biological, they provoke ionization of existent molecules in the cells. That ionization can drive to abnormal chemical reactions and the destruction of the cell or alteration of its functions. In the systemic interaction, the absorbed doses work as main causers of possible lesions to the human beings. Mainly, when the organs reproducers are exposed for long periods or for absorption of discharges radiation doses, could bring consequences so much somatic (to the own individual-short period) as genetics (lesions that commit to the formation of the future generations-of long period). Therefore, they appear damages provoked by the radiation that they can nucleus, provoking them damages, whose effects appear in short and long period. In synthesis the effects in an individual depend on the absorbed dose, of the frequency and in the exhibition way-whole or located body. Finally, the ionizing radiations can act harmfully in the molecules if, the amount of absorbed of radiation dose be absorbed directly by the molecules that are essential in the several cellular metabolisms.
Keywords: Radiation ionizing; effects; human beings